MEMBACA PUISI DENGAN METODE MEMBACA ESTETIK PADA SISWA SMK N 1 SLAWI - Sari, Vita Ika; Triana, Leli; Nirmala, Afsun Aulia; Anwar, Syamsul (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
This dedication shows that the lack of stability of the concept and aesthetic reading process is one of the obstacles that inhibits the fostering of the appreciation of the literature of students of SMK N 1 Slawi. The purpose of this dedication is 1) Identifying the ability to read literary texts, especially reading poetry in students of SMK N 1 Slawi. 2) Describe the application of aesthetic reading in literary learning, especially reading poetry at SMK N 1 Slawi. The method used in this service is a qualitative instrumental approach. Where this dedication will produce new methods in reading aesthetics. The sample in this service is class XI student of SMK N 1 Slawi. Data collection techniques used were observation, interviews, observations on all parties involved in the implementation of this service. The results of this dedication of 10% of students are able to read poetry well and by 90% of students have not been able to read poetry well in the first meeting. There was an increase in the ability to read poetry after being given aesthetic reading stimulus by the team, that is 70% of students were skilled in reading poetry and 30% of students had difficulty in determining gestures and appreciation.